(untitled) (Revista Científica Integrada, 2025)
Objective: To analyze the knowledge of university student mothers about postpartum depression. Method: A descriptive study with a qualitative approach, developed in a Higher Education Institution located in the Central-West region of Brazil, through interviews. Participants were student mothers enrolled in undergraduate courses, including those over 18 years of age who had a connection with the university during the immediate, intermediate, or postpartum period, and excluding those with any mental condition that prevented them from participating in the research. The sample was selected using the Snowball sampling technique. Data analysis was performed using the Descending Hierarchical Classification method of the IRAMUTEQ software and Bardin’s content analysis. Results: Sixteen mothers were interviewed, with a mean age of 23.4 years, predominantly students of the Nursing course (43.75%). The analysis revealed the categories named “Maternal Experience and Knowledge of University Mothers about Postpartum Depression” and “Prevention and Coping Strategies.” Conclusion: Mothers’ perception of the topic is vague, and postpartum depression is commonly confused with symptoms of baby blues. It is understood that it is the responsibility of healthcare professionals to create prevention strategies, train and inform people about postpartum depression, so that they can be minimally prepared to deal with the changes in life and routine after childbirth.